Factors associated with an excellent transfer of passive immunity: multisite, cross-sectional study conducted in different European countries on dairy cattle - Fernandez-Novo, Aitor; Kolkman, Iris; Driesse, Monique; Yarnall, Matt; Cerviño, Manuel; Dieguez, Francisco Javier; Astiz, Susana (Frontiers in Veterinary Science, 2025)
Transfer of passive immunity (TPI) is key to achieving a good immunity status in newborn calves. The traditional scientific approach examines risk factors for the failure of TPI, but the benefits of achieving an excellent transfer of passive immunity are well recognized, justifying a closer examination of specific influencing factors. However, there is scarce information about conditions related to an excellent TPI, which may differ from those avoiding failure. Therefore, the objective of this work was to detect factors determining an excellent transfer of passive immunity. From April to July 2022, 1,041 calves from 108 European farms from six countries were studied. Colostrum quality and level of passive immunity in calves were indirectly measured with refractometry. Data of colostrum management, dam, calf and farm conditions were recorded. A categorization of poor, fair and excellent TPI were established. Mixed-effects multinomial regression modeling was implemented at animal-level, with country and herd as random factors. Median values for colostrum variables were 3 l of volume, quality of 24.4% Brix and time to administration after birth of 2 h. Only one country achieved >40% of calves in the excellent category. Mean factors affecting excellent TPI were volume and quality of the colostrum administered. In conclusion, although most farms in Europe manage and administer adequately colostrum, there are aspects to improve to achieve more than 40% of calves within the excellent category. These key factors align with those preventing failure of TPI, although this result should be taken into account with prudence based on the limitations of the study.